Teachers’ perceived stress and experience in online teaching during the early phase of the COVID-19 pandemic - Beara, Mirjana; Rakić-Bajić, Gorana; Hinić, Darko (Psihološka istraživanja, 2021)
Stress affects various aspects of human life and may also affect professional functioning of teachers. Research on attitudes towards digital/online teaching and learning has shown that the success of any online education depends upon the attitude of teachers towards online learning. Some studies before the pandemic showed that teachers, in comparison to other high-stress occupations, were reported as being the most stressed in regard to physical and psychological wellbeing. The aim of this pilot study is to investigate teachers’ perceived stress and its relationship with attitudes towards online teaching and subjective online teaching overload during the early phase of COVID-19 pandemic. The online survey was performed during and immediately after the enforcement of lockdown measures in Vojvodina in spring 2020. The total sample included 64 teachers from primary and secondary schools (12.5% class teachers), between 26 and 63 years of age. The subjective stress perception was measured using the Perceived Stress Scale, and a 19-item questionnaire was constructed for the assessment of attitudes towards online teaching. The perceived stress level was increased compared to the norms suggested by the scale author. Subjective overload with online teaching was significantly positively correlated with the perceived stress (r = .385, p < .01). Teachers did not report extremely positive or negative attitudes towards online teaching. Still, the attitude towards online teaching was significantly negatively correlated with the subjective overload with online teaching (r = - .294, p < .05). Results showed no significant correlation between the perceived stress and attitudes towards online teaching.
Keywords: teachers; online teaching; perceived stress; attitudes towards online teaching; online teaching overload